Methodological innovations at the intersection of video-based educational research traditions: Reflections on relevance, data selection, and phenomena of interest. Issue 1 (1st January 2023) - DeLiema, David; Hufnagle, Ashley; Rao, V.N. Vimal; Baker, Justin; Valerie, Jesslyn; Kim, Jasmine
ABSTRACT: Approaches to discourse analysis in educational research tend to operate within the boundaries of particular video-based research traditions. We examine four of these traditions that are especially relevant to the learning sciences – conversation analysis, discursive psychology, interaction analysis, and video-cued ethnography – and instead of assuming that they are incommensurate, we examine their interconnections and areas of synthesis to make space for methodological innovations. In looking for unforeseen or de-emphasized points of synergy, we consider four approaches to each tradition: (1) making claims about internal processes; (2) inviting research participants to reflect on the video records; (3) formulating conjectures about the video data; and (4) noticing and documenting patterns. We examine the above approaches in the context of a research-practice partnership between educational researchers and a non-profit organization focused on outdoor family play, focusing in particular on autonomy-supportive parenting. Through this methodological reflection, we raise a number of novel considerations regarding how video-based educational researchers can understand what is relevant to the participants, engage with data selection, and formulate claims about recognizable phenomena in the data. We conclude by discussing problems of practice in video-based educational research that this mixed-tradition approach can address.